James K. A. Smith. You Are What You Love: The Spiritual Power of Habit. - Denis Kondyuk (Богословські роздуми: Східноєвропейський журнал богословʼя)
Book review: You Are What You Love: The Spiritual Power of Habit. By James K. A. Smith: Brazos Press, 2016, xii + 210 pp.; ISBN 9781587433801 (cloth); 20.00 USD.